The neural mind debate - Oviedo, Lluís; Innocenti, Giorgio (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
LLUÍSOVIEDO: The example you put on, the tennis sport man playing with health conscious collaboration is just the same example that Antonio Damasio offers in this new book justto rebuke Libert and all his followers against consciousness.